(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The research aims to study the marketing costs in its various items, which are important costs as it specializes in tunnels on the marketing side through which the company’s services are introduced to ensure that these services reach as many segments of society as possible, which serves the company’s objectives and expand its business and increase its market share. As well as the definition of profitability and its relation to marketing costs in the portfolios of the national insurance company. The research hypothesis was formulated to study and analyze the relationship and impact between the marketing costs and profitability of the research sample company. The research sample was determined by the National General Insurance Company and the Spss(22) statistical program was used to extract the marketing costs of a number of national insurance company portfolios for a period of (2011-2018) as well as the profitability of the net profit of the portfolio. As for the most prominent results of the research despite the importance of the marketing thought of all institutions and their role in the process of promoting the product or service, but the practical awareness in the application and use of marketing programs is still in our institutions, especially insurance suffers from a lack of attention within the priorities of the institution key. As for the most prominent results of the research despite the importance of the marketing thought of all institutions and their role in the process of promoting the product or service, but the practical awareness in the application and use of marketing programs is still in our institutions, especially insurance suffers from a lack of interest within the priorities of the institution.